Managing the sublime aesthetic when communicating an assessment regime: The Burkean Pendulum - Kofinas, Alexander (Management Learning, 2018)
The importance of understanding students’ engagement is prominent in higher education. Assessment is the main driver of student engagement, a phenomenon known as backwash. I propose in this paper that students’ engagement with learning is often driven by an aesthetic motivation. I establish the connections between Burke’s (and Kant’s) conceptualisation of aesthetics as a dichotomy of beauty and the sublime (which I label the Burkean Pendulum) to motivation. I explore the links between this aesthetic motivation and the assessment regime focussing on the Burkean/Kantian sublime and suggest four communication strategies that can help manage the sublime when it arises in students’ education journeys. Thus, my contributions are twofold: firstly, I introduce the Burkean Pendulum as a means for educators to reflect on the aesthetic aspects of their designed assessment regimes. Secondly, I propose a framework of communication strategy narratives (Thriller, Horror, Exploration and Action) that could be used to manage the sublime of the assessment regime.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMzUwNTA3NjE3NzM4ODY0